Effect of bromelain and papain gel on enamel deproteinisation before orthodontic bracket bonding - Pithon Matheus Melo; Campos Matheus Souza; da Silva Coqueiro Raildo (Sciendo, 2016)
To test the hypothesis that enamel surface deproteinisation with different concentrations of bromelain in association with 10% papain increases the shear bond strength (SBS) of brackets bonded with orthodontic composite and resin modified glass ionomer cement (RMGIC).